Objective PET study of glucose metabolism asymmetries in children with epilepsy: Implications for normal brain development - Pilli, Vinod K.; Jeong, Jeong‐Won; Konka, Praneetha; Kumar, Ajay; Chugani, Harry T.; Juhász, Csaba (Human brain mapping, 2019)
Clinical interpretation of cerebral positron emission tomography with 2‐deoxy‐2[F‐18]fluoro‐d‐glucose (FDG‐PET) images often relies on evaluation of regional asymmetries. This study was designed to establish age‐related variations in regional cortical glucose metabolism asymmetries in the developing human brain. FDG‐PET scans of 58 children (age: 1–18 years) were selected from a large single‐center pediatric PET database. All children had a history of epilepsy, normal MRI, and normal pattern of glucose metabolism on visual evaluation. PET images were analyzed objectively by statistical parametric mapping with the use of age‐specific FDG‐PET templates. Regional FDG uptake was measured in 35 cortical regions in both hemispheres using an automated anatomical labeling atlas, and left/right ratios were correlated with age, gender, and epilepsy variables. Cortical glucose metabolism was mostly symmetric in young children and became increasingly asymmetric in older subjects. Specifically, several frontal cortical regions showed an age‐related increase of left > right asymmetries (mean: up to 10%), while right > left asymmetries emerged in posterior cortex (including portions of the occipital, parietal, and temporal lobe) in older children (up to 9%). Similar trends were seen in a subgroup of 39 children with known right‐handedness. Age‐related correlations of regional metabolic asymmetries showed no robust gender differences and were not affected by epilepsy variables. These data demonstrate a region‐specific emergence of cortical metabolic asymmetries between age 1–18 years, with left > right asymmetry in frontal and right > left asymmetry in posterior regions. The findings can facilitate correct interpretation of cortical regional asymmetries on pediatric FDG‐PET images across a wide age range.